2002
DOI: 10.1055/s-2002-30103
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of Antimicrobial Agents

Abstract: Antimicrobial agents are a common and important cause of hepatotoxicity. As a class, the antimicrobials contain many and varied structures, leading to a wide clinical spectrum of hepatotoxicity. Minor liver injury, manifest only as liver enzyme elevations, is common with some antimicrobials. Clinically significant injury is unusual but can adopt almost any form. Classical acute hepatocellular, cholestatic, or mixed reactions are most often seen. Other forms of hepatotoxicity including granulomatous reactions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…The development of hepatitis 4-6 weeks after drug ingestion in both cases is consistent with prior reports of B-lactam associated hepatotoxicity (2,3). Neither patient had prominent features of a hypersensitivity reaction such as fever and eosinophilia that has been reported in up to 50% of patients with amoxicillin/clavulanate hepatotoxicity (4,5). However, review of available liver histology demonstrated histological features compatible with a severe drug induced hepatitis in both cases (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The development of hepatitis 4-6 weeks after drug ingestion in both cases is consistent with prior reports of B-lactam associated hepatotoxicity (2,3). Neither patient had prominent features of a hypersensitivity reaction such as fever and eosinophilia that has been reported in up to 50% of patients with amoxicillin/clavulanate hepatotoxicity (4,5). However, review of available liver histology demonstrated histological features compatible with a severe drug induced hepatitis in both cases (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…A delayed cholestatic or mixed hepatocellular-cholestatic liver injury pattern has typically been reported with amoxicillin/clavulanate that usually has a benign course and resolves within 2 months (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…14,18 The combination of Cefixime+Clavulanic acid have caused increased liver enzymes in 7 patients, our finding well supported by previous studies showing Semisynthetic penicillins are frequent causes of hepatotoxicity, especially when combined with clavulanic acid. 19 Interstitial nephritis was also found in our study in patients consuming β-Lactam antibiotics (Amoxycillin). The findings of this study were in accordance with recent studies showing β-Lactam antibiotics causing Interstitial nephritis.…”
Section: Discussionsupporting
confidence: 78%
“…Although this is true for some drugs (e.g., estrogens induce cholestatic injury and seldom any present with any other pattern of damage), for most other drugs such consistency is not so clear. For instance, amoxicillin-clavulanate tends to produce cholestatic or mixed damage, although hepatocellular damage has been repor ted frequently as well [16,54] . Hepatocellular and cholestatic or mixed injury have been noted with nimesulide [55] or troglitazone [56,57] , among others.…”
Section: Cur Rently the Only Way To Confidently Confir M I D I O S Ymentioning
confidence: 99%